Total abdominal robotic approach for level 4 inferior vena cava thrombus in renal cell carcinoma - Kishore Thekke Adiyat; Jeni Mathew; Venkata Bhargava Bopanna; Shilpa Omkarappa; Sangeeth Srinivasan; Biju Chandran (Urology Video Journal)
Objective: This study aims to elucidate the technique involved in employing a total robotic approach for managing level 4 inferior vena cava (IVC) thrombus. Patient and surgical procedure: A 71-year-old female presented with a 12 × 9 × 8 cm left renal mass with a thrombus extending into the atrium. Utilizing the Da Vinci Si system (Intuitive Surgical, Sunnyvale, CA), the surgical procedure commenced with the patient in a right lateral position, undergoing left radical nephrectomy, stapling of the renal vein, and distal pancreatectomy due to tumour infiltration. Subsequently, with the patient in the left lateral position, delivery of the left renal vein stump, isolation of the right renal artery/vein, and mobilization of the right lobe of the liver were performed. The patient was then placed in the supine position for further dissection of the suprahepatic IVC. To enhance exposure of the suprahepatic IVC, the central tendon of the diaphragm/pericardium was divided. Sequential clamping of the infrarenal IVC, right renal vein/artery, and porta was performed. The thrombus was gently maneuvered from the atrium to the suprahepatic IVC under real time ultrasound guidance and subsequently extracted through cavotomy with excision of the renal vein stump. Closure of the IVC was then performed. Results: The total operative time was 420 min, with console time comprising 290 min. Porta clamp time was 11 min, while the right renal clamp time was 22 min. Blood loss was 375 ml and the patient's hospital stay lasted 8 days. Pathological examination confirmed clear cell renal carcinoma PT4N0M0, Furhman Grade 2. Conclusion: The total robotic approach for managing level 4 IVC thrombus, involving the division of the central tendon of the diaphragm, demonstrates feasibility and represents a promising surgical technique.